What could have been estimating the economic impacts of Typhoon Yolanda in Region VIII - Julian, Shiely Anne O. (School of Economics, University of the Philippines Diliman, 2019)
Every year, typhoons wreak havoc on the lives of many people and on local economies. One of the most devastating in recent years is Typhoon Yolanda (Haiyan) which is reported to have caused 6,300 deaths and approximately Php 95 billion in direct economic losses (NDRRMC, 2013). Harder to estimate are the losses in future economic welfare due to current damages in productive physical and human capital brought about by the typhoon. Here we present an estimate of its impact on the economy of Region VIII as measured by the region_s Gross Regional Domestic Product (GRDP) per capita. We do this by adopting the Synthetic Control Method developed by Abadie et al. (2010) to construct a counterfactual of Region VIII, revealing how the region would have performed without Yolanda. We use three models that restricted our donor pools for the synthetic control to (1) non_Yolanda_affected regions, (2) regions that are at par with Region VIII_s characteristics and unaffected by the typhoon, and (3) regions spared from Yolanda that experienced a drop in GRDP from 2011_2012. Our results show that on average, Region VIII fared lower than the constructed synthetic Region VIII by Php 716.76 (constant 2000 price) on the first four years after the disaster (2014_2017). In other words, Region VIII had a total economic per capita loss of Php 2,867.03 in constant prices or Php 5,156.93 in current 2013 prices. Comparing it with the per capita cost of damages for Region VIII, Php 8,217.87 in constant prices and Php 13,699.19 in current prices, these figures seem miniscule compared to the reported losses and damages of Yolanda. We reiterate that the measure used accounts only for the lost income (and not for the lost wealth and welfare) of the Yolanda_stricken population.